A communication model for nursing staff working in dementia care: Results of a scoping review. (January 2021) - van Manen, Annick S.; Aarts, Sil; Metzelthin, Silke F.; Verbeek, Hilde; Hamers, Jan P.H.; Zwakhalen, Sandra M.G.
Abstract: Background: Communication between nursing staff and people with dementia can be challenging. According to the literature, communication is seen as a process of social- and/or informational exchange between a sender and a receiver in a context. Factors related to these elements determine the quality of communication. Insight into the factors involved in the communication process between nursing staff and people with dementia is limited and a comprehensive model of communication in dementia care is lacking. Objectives: To identify and visualize factors associated with communication between nursing staff and people with dementia. Design: A scoping review of scientific literature. Data Sources: Scientific articles were retrieved from the bibliographic databases of PubMed, CINAHL and PsycINFO. Review Methods: The reviewing process was directed by the Joanna Briggs guidelines for scoping reviews. Full-text articles describing the communication process between nursing staff and people with dementia were eligible for inclusion. A data extraction form was used to identify factors associated with communication. Following a directed content analysis approach, factors were categorized in one of three categories: nursing staff; people with dementia; or context. Each category was thematically analysed to identify themes and subthemes. Results were visualized into a communication model. Results: The review included 31 articles; in total, 115 factors were extracted. Thematic analysis of nursing staff factors ( n = 78) showed that communication is associated with professional characteristics, individual experiences, verbal - and non-verbal communication skills, communication approach and values . Factors attributed to people with dementia ( n = 22) concerned client characteristics, functional status, behaviour, verbal communication skills and values . Contextual factors ( n = 15) related to organization of care, time and situation . Based on these results, the Contac-d model was constructed. Conclusions: The Contac-d model gives a comprehensive overview of factors involved in the communication process between nursing staff and people with dementia, providing insight in potential starting points for communication improvement, e.g. respect for needs, identity and privacy of people with dementia, a flexible and adapted communication approach and matching language. Additionally, results suggest that an appealing location, longer duration of the interaction, and music in the surrounding may improve communication in certain situations. However, it was not feasible based on current literature to recommend what works to improve communication in which situations. Future studies should study factors and their interrelatedness in specific care situations. Authors further believe that more attention should be paid to strengths and capabilities of people with dementia and to non-modifiable factors that influence communication.